Intelligent electromagnetic actuated continuously variable transmission System - Rahman, Mohammed Ataur (2017)
Embodiments of the present invention relate to transmission systems for a motor vehicle, and more particularly, to a continuously variable transmission system (Hereinafter referred to as “CVT”) for a motor vehicle. The present invention aims to provide transmission systems for a motor vehicle, and more particularly, to provide a continuously variable transmission system for a motor vehicle. A continuously variable transmission system for a vehicle includes a primary pulley operatively coupled to an engine of the vehicle, a primary cylinder positioned on the primary pulley for adjusting a transmission rate thereof, a secondary pulley operatively coupled to multiple wheels of the vehicle, a secondary cylinder positioned on the secondary pulley for adjusting a transmission rate thereof, a drive belt operatively wound over the primary pulley and the secondary pulley for transmitting power of the engine of the vehicle to the multiple wheels of the vehicle, and a control module for controlling the continuously variable transmission system for the vehicle. In one embodiment of the present invention, the control module includes a primary control valve for generating a primary control pressure for the primary cylinder, a secondary control valve for generating a secondary control pressure for the secondary cylinder, a controlling mechanism coupled to the primary control valve and the secondary control valve for changing the primary control pressure and secondary control pressure, and an actuator positioned on the primary control valve for receiving an electric signal from the controlling mechanism. In one embodiment of the present invention, the system further includes an electromagnetic solenoid responsive to the electric signal for decreasing the primary control pressure. The electromagnetic solenoid is configured for pushing and pulling the primary pulley and the secondary pulley with the drive belt positioned therebetween. The operation of the electromagnetic solenoid is performed by controlling eddy current. The operation of the electromagnetic solenoid is performed by employing a battery, a sensor and a potentiometer. In one embodiment of the present invention, the electromagnetic solenoid moves the primary pulley and the secondary pulley with the drive belt positioned therebetween at about 0.01 seconds. While the invention is described herein by way of example using several embodiments and illustrative drawings, those skilled in the art will recognise that the invention is not limited to the embodiments of drawing or drawings described, and are not intended to represent the scale of the various components. A system for controlling a continuously variable transmission in a vehicle is disclosed. The system comprising: a primary and secondary variable diameter pulleys (5, 4) linked by a flexible drive member (10); a power supply (15); and an electromagnetic actuator coupled to the power supply (15) for controlling a gear ratio of the primary and secondary pulleys (5, 4), wherein the electromagnetic actuator system comprising: at least one electromagnetic solenoid (1, 2) connected to the pulley (5, 4); a detecting unit for detecting at least one operating condition of the vehicle; a processing unit configured to set a target gear ratio based on the detected operating condition of the vehicle; and a control unit for controlling the current from the power supply (15) to the electromagnetic solenoid (1, 2) to shift the current gear ratio to the target gear ratio.